PERFORMANCE MANAGEMENT OF HAJJ SERVICES AT THE OFFICE OF THE MINISTRY OF RELIGION OF KUBU RAYA REGENCY - Putri Handayani Nasution; Raziki Waldan; Amalia Irfani; Lukmanul Hakim; Diena Juliana (J-MD Jurnal Manajemen Dakwah, 2025)
Effective and efficient Hajj services require a structured performance management system. This study aims to identify and analyze the stages of performance management, including planning, management, evaluation, and appreciation, in the Hajj services at the Office of the Ministry of Religious Affairs of Kubu Raya Regency. A qualitative approach with a descriptive method was employed. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. Data validity was ensured through triangulation. The findings indicate that Hajj services have been implemented systematically in accordance with performance management stages, beginning with the preparation of a Performance Agreement (PERKIN) as the planning stage, routine management by the head of the organizer supported by the Integrated Hajj Computerization Information System (SISKOHAT), and structured evaluations for continuous improvement. Employee performance is appreciated through awards in the form of certificates or plaques. These findings imply that a comprehensive performance management implementation can enhance the quality of public services, particularly in the administration of Hajj and Umrah. The novelty of this study lies in the integration of digital information systems throughout all stages of Hajj service performance management at the regency level.